2022
DOI: 10.1021/acsami.1c21814
|View full text |Cite
|
Sign up to set email alerts
|

In-Line Characterization of the Temperature-Responsive Behavior of Surface-Bound Microgel Coatings by QCM-D: A Novel Strategy for Protein Repellence Evaluation

Abstract: In this work, quartz crystal microbalance with dissipation monitoring (QCM-D) was used to develop a new method to evaluate the protein repellency of microgel coatings. Compared to traditional protocols for surface analysis, QCM has the advantage of a real-time quantitative approach with high sensitivity, allowing us to describe variations of the adsorbed mass with unprecedented accuracy. To enable the detectability of the film throughout the whole operational temperature interval, a poly(Nisopropylacrylamide-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…Finally, experimentally, competitive adsorption of additives compared to PEG 400 oil was confirmed via the dissipative quartz crystal microbalance (QCM-D) test. It is well known that the frequency shift (Δ f ) and mass change (Δ m ) are directly proportional to the QCM-D test, which can be described by the Sauerbrey formula. , Thus, the adsorption kinetic of the lubricant additive on the gold chip can be directly reflected on the Δ f span, indicating the interactions between COFs and the chip. As depicted in Figure d, in an ethanol atmosphere where either PEG 400 or each COF additive is introduced, the curve of frequency presents an instant and steep decrease, indicating that a strong interaction between gold atoms and each adsorbate occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, experimentally, competitive adsorption of additives compared to PEG 400 oil was confirmed via the dissipative quartz crystal microbalance (QCM-D) test. It is well known that the frequency shift (Δ f ) and mass change (Δ m ) are directly proportional to the QCM-D test, which can be described by the Sauerbrey formula. , Thus, the adsorption kinetic of the lubricant additive on the gold chip can be directly reflected on the Δ f span, indicating the interactions between COFs and the chip. As depicted in Figure d, in an ethanol atmosphere where either PEG 400 or each COF additive is introduced, the curve of frequency presents an instant and steep decrease, indicating that a strong interaction between gold atoms and each adsorbate occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Quartz crystal microbalance with dissipation (QCM-D) is a measurement technique, which is nowadays widely utilized for investigation of hard and soft interfaces. The measurement technique can monitor in situ changes in interfacial molecular organization and is tolerant to several types of different adsorbents ranging from inorganic to organic molecules, macromolecules, or discrete nanosized objects in the size range ∼1 nm to 1 μm, and the technique can be applied for several liquids. This makes the QCM-D technique one of the most versatile and key research technologies for the investigation of dynamics of soft, solvated interfaces. , Especially the investigation of dynamic response becomes very attractive with the QCM-technique, which includes the response investigation of nano- and microstructural materials on different stimuli such as pH, , temperature, light, or chemical gradients. However, the QCM-D investigations of photosensitive soft interfaces with respect to light triggered dynamic changes in interfacial properties have not been widely reported, since the quartz crystal itself is quite sensitive to illumination. Under exposure to light a frequency and dissipation shift is seen (see example plot in Figure ) and has been reported in the literature as the “light induced detuning” (LID). The LID depends on many parameters such as light power and wavelength as well as on surrounding conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[26,27] Recently, Santi et al have reported the synthesis of poly(2-methacryloyloxyethyl phosphorylcholine) (PMPC)-based microgels via surface grafting of already synthesized microgels, which showed high extents of antifouling activity. [28] Therefore, our motivation for this work stems from the hypothesis that increasing the zwitterionic loading in microgels would further improve the anti-fouling efficacy of the microgels. Though there have been recent research efforts that have proved the feasibility of synthesis of colloidally stable nanogels containing hydrophilic polyethylene glycol (PEG)based macromonomers, zwitterions by the virtue of being far superior to PEG-based materials in terms of anti-fouling properties, should incite greater interest among the biomedical research community.…”
Section: Introductionmentioning
confidence: 99%